Development of fuzzy inference system in predictive maintenance architecture for broadcasting chain. (21st January 2022) - Sahba, Rezvaneh; Radfar, Reza; Ghatari, Ali Rajabzadeh; Ebrahimi, Alireza Pour
This paper offers an innovative predictive maintenance (PdM) framework based on advanced reference architecture model Industry 4.0 (RAMI 4.0) to decrease maintenance costs and time based on design science research (DSR) in real-time monitoring cases. The offered framework endures the predictable failures in similar manufacturing by utilising a combination of the fuzzy inference system (FIS) method and analytic hierarchy process (AHP) based on root cause experts' knowledge. Most very high critical alerts are related to communication link stability. Practical investigations have been developed in the Islamic Republic of Iran Broadcasting's (IRIB) high-power station to appraise the functionality and compatibility of the proposed PdM framework. Practical outcomes emphasise the importance of asset layer and communication link in PdM management.